Effects of different exercise modalities on blood pressure and endothelial function in prehypertension individuals: a systematic review and network meta-analysis - Yang, Yingtian; Lv, Qianyu; Hou, Xinzheng; Lv, Yanfei; Zhang, Xirui; Wu, Qian; Ye, Xuejiao; Yang, Chenyan; Huang, Mingyu; Wang, Shihan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the relative impacts of various exercise protocols on blood pressure (BP) and endothelial function in prehypertension individuals.MethodsIn this systematic review and network meta-analysis (NMA), PubMed, Cochrane Library, Web of Science, Embase, CINAHL, SPORTDiscus, and Rehabilitation & Sports Medicine databases were searched until September 12, 2024. Randomized controlled trials that examined the effectiveness of exercise treatments on people with prehypertension compared to a non-exercise control group or other exercise modes were included. A Bayesian NMA were applied to examine SBP, DBP, flow-mediated dilation (FMD), and pulse wave velocity (PWV). The surface underneath the cumulative ranking curve data was utilized to rate interventions. Confidence was evaluated using the CINeMA framework.ResultsA total of 18 articles with 2,592 individuals were included in the NMA. Tai Chi demonstrated the greatest decrease in SBP of −8.67 mm Hg [95% credible interval (CI): −17.29 to −0.05], while isometric exercise training (IET) exhibited the most substantial enhancement in DBP of −4.61 mm Hg (95% CI: −8.11 to −1.11) and PWV of −0.82 m/s (95% CI: −1.58 to −0.06). Moderate-intensity continuous training yielded the largest improvement in FMD at 5.82% (95% CI: 5.41–6.22).ConclusionDiverse exercise modalities can enhance BP and vascular function in prehypertensive patients. Overall, Tai Chi and IET are the most productive exercises for reducing BP, with IET being particularly effective in diminishing arterial stiffness. MICT stands out in enhancing endothelial function. Nevertheless, further comprehensive studies encompassing more diverse exercise treatments are necessary to ascertain the best exercise patterns and dosing strategies.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=614765, identifier: CRD42024614765.